ANALISIS FAKTOR PENYEBAB DAN PENANGGUTANGAN TINDAK PIDANA PERKOSAAN DATAM KELUARGA - Firganefi, Firganefi (PRAEVIA, 2011)
The purpose of research is to analyze the factors that can cause rapping criminal act in family and the way of its prevention . The methodology of research is normative and empirical jurisdiction. The result of research indicates that the causal factors of rapping criminal act in family consists of internal and external factors, The prevention can use penal and non penal procedures.